Affinity Determination of Monoclonal Antibodies (mAbs) Using Enzyme- Linked Immunosorbent Assay (ELISA); A Protocol - Mansouri, Mansoure; Mohammadi, Mehdi; Montazer, Fatemeh; Jeddi-Tehrani, Mahmood; Shabani, Mahdi (Student Research in Translational Medicine, 2024)
Monoclonal antibodies (mAbs) have changed diagnostics and therapy due to their high specificity and affinity to the target antigens (Ags). Accurately measuring the affinity of mAbs is critical to understanding their binding properties. It represents the strength of binding between an antibody (Ab) and its target Ag and enables decision making in the development and optimization of these antibodies to improve their efficacy in diagnostics and therapy. Various methods such as the equilibrium dissociation constant, ELISA, surface plasmon resonance (SPR), and microarray-based platforms can be used to determine mAb affinity. The non-competitive ELISA is simple and available method for many laboratories, based on the law of mass action that compares the OD50 of three sigmoidal curves of serial Ab dilutions on plates coated with different Ag concentrations to determine the binding strength between a mAb and its Ag. This protocol provides a step-by-step guide to determining mAb affinity using modified ELISA and enables researchers to make informed decisions about the development and application of mAbs in their respective fields.